Muslims and Indian National Congress : Badruddin Tyabji and his times - Shakir, Moin. (Delhi : Distributors, Ajanta Books International, 1987)
Biographical sketch of Badruddin Tyabji, 1844-1906, eminent jurist and leader in the Indian freedom movement.
Bibliography: p. [82]-84.
Keywords: Tyabji, Badruddin; Muslims -- Political activity -- India; Indian National Congress -- History; Politicians -- India -- Biography; India -- Politics and government -- 1857-1919.